Soil conservation practices in three watersheds of Benin: Farmers’ cropping systems characterization - KOUELO ALLADASSI, FÉLIX; HOUNGNANDAN, PASCAL; DEDEHOUANOU, HOUINSOU; TOSSOU, COCOU RIGOBERT; BELLO, OROU DAOUDA; BEKOU, AFIOLOROM KOSSOBAKAN JOEL; TCHETANGNI, YENAKPON ANSELME (My University, 2016)
This document addresses the farming practices and their characteristics on three watersheds in southern Benin. These watersheds are located in the villages of Govié, in Allada district, Lokogba in Aplahoué district and Linsinlin in Djidja district. Simple random sampling is used to investigate 417 farm households at the rate of 139 per village. Focus groups are conducted with resource persons and individual interviews according to a survey tool. The observation unit of the survey is the head of the farm household. In the villages of Lokogba and Linsinlin, farm households practice slash and burn agriculture in contrast to those of the village of Govié where residues are not burned. Soil conservation practices (direct sowing, minimum tillage) are made in the village of Lokogba while tillage is widely practiced in the other villages. In the village of Govié, some households use mulch and mineral fertilizers, but the rate is low. Organic fertilizers are used by 40.2% of farmers in Lokogba village. Crop rotation and fallow are still widely practiced in this village by 85.6 and 84.6% of the surveyed households respectively. In other villages, these practices are absent or present at very low levels showing their high level of agricultural intensification. Weeding is the main preventive measures used by farmers in village of Govié (38.8%), Lokogba (93.8%) and Linsinlin (23.2%). Chemical pests control is used by all farmers of village of Linsinlin and Lokogba. The farming practices are significantly specific to the surveyed villages. Soil conservation practices are more observed at Govié than Lokogba. In the village of Linsinlin, these practices are almost absent.
Keywords: Soil conservation; farming practices; cropping systems; watersheds; Benin